Поховання у сидячому положенні на території Південної Русі - Бібіков, Д.В. (Археологія і давня історія України, 2021)
Стаття присвячена південноруським похованням Х—ХІ ст., здійсненим у сидячому положенні.
Аналіз їх речового набору та обрядових рис дозволяє
простежити шляхи трансформації цього звичаю,
а також — зміну соціального та етнічного складу похованих. The article is devoted to the burials of the X—XI centuries,
where the deceased were found in a sitting position.
Despite the fact that this custom itself is undoubtedly
of Norman origin, the issue of ethnic and social attribution
of most complexes from the territory of Southern
Rus’ has not received appropriate attention among the
researchers. Information was collected on 17 Southern
Rus’ burials, which, according to some researchers, were
carried out in a sitting position. However, it is not always
possible to establish the posture of the deceased
with complete confidence. The basic variants of mutual
arrangement of bone remains are allocated and on their
basis the most widespread ways of giving to a body a sitting
position are reconstructed.
Both by the social composition of the buried and
chronologically, the burial complexes can be divided
into two separate groups. The first group includes rich
burials in chamber tombs. All of them are dated by the
X century and are located in the necropolises of Kyiv
and Shestovytsia, two points of the highest concentration
of the Scandinavian ethnic component in Southern
Rus’. A wide range of objects of Scandinavian origin
was found in the toms, there are burials with weapons,
slaves and horses killed. Undoubtedly, the dead belonged
to the military-trade elite. In combination with
chamber tombs, a sitting posture can be an indicator of
the Scandinavian origin of the dead.
Sedentary burials of the second group are located in
the peripheral areas of the Southern Rus’ and belong to
the Christian era (approximately — the end of the X—
XI centuries). Burials are carried out at the level of the
day surface, are marked by rather «poor» inventory and,
as a rule, do not have burial structures. They can be associated
with the ordinary Slavic population and its efforts
to recreate certain prestigious features of the funeral
rites of the previous period. Probably, the sedentary position
symbolized a dominant status in society, and in the
funeral rite carried only a social, not a religious stress.